2013 XV Symposium on Virtual and Augmented Reality 2013
DOI: 10.1109/svr.2013.46
|View full text |Cite
|
Sign up to set email alerts
|

Context-Aware Virtual Laboratory for Teaching Computer Networks: A Proposal in the 3D OpenSim Environment

Abstract: Technological advances have created new possibilities in education, requiring the development of new pedagogical practices that contribute to the process of teaching and learning. This paper presents a proposal for the construction of an immersive virtual laboratory of computer networks in 3D OpenSim environment. The main advantages of the proposal are the development and the treatment of issues related to context-aware computing, such as: cognitive styles; technology used; analysis of learning; expertise and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…It consists of test benches with computers, racks with routes, etc. Also, virtual tutor is present in the form of avatar (Voss, Nunes, Muhlbeier, & Medina, 2013). …”
Section: Opensimulatormentioning
confidence: 99%
“…It consists of test benches with computers, racks with routes, etc. Also, virtual tutor is present in the form of avatar (Voss, Nunes, Muhlbeier, & Medina, 2013). …”
Section: Opensimulatormentioning
confidence: 99%
“…Ref. [68] concluded that the advent of Virtual Laboratories had introduced easiness into the practice of electrical circuit building and made it fun for both students and lecturers, thereby making the user have positive thoughts towards the Virtual Laboratories practices.…”
Section: A the Level Of Awareness Among Electrical Engineering Lecturersmentioning
confidence: 99%
“…Virtual lab is one of the popular technologies followed by many educational institutions [11]. It is nothing but virtual environment for the labs and virtual labs can be accessed by the user from anywhere that"s the only advantage it has.…”
Section: Virtual Labmentioning
confidence: 99%